The role of qualitative research in management - C. Orpen (South African Journal of Business Management, 1987)
It is argued that there are currently two separate research approaches to behaviour in organizations; the qualitative approach and the quantitative approach, each with their own framework, criteria of proof, and accepted procedures. Reasons for the dominance of the quantitative approach and the renewed interest in the qualitative approach are presented. Implications for future research in organizational behaviour are developed. There is a need for more multi-approach research efforts and for a conceptual scheme that will locate the two approaches in relation to one another.
Keywords: 650